Exploration of Productivity, Chemical Composition, and Antioxidant Potential of Origanum vulgare L. Grown at Different Geographical Locations of Western Himalaya, India - Shweta Goyal; Geeta Tewari; H. K Pandey; Anjali Kumari (Journal of Chemistry)
Origanum vulgare L., the most complex and variable species of the genus Origanum, is used to cure various diseases in the traditional medicinal system. In the current investigation, O. vulgare was collected from its natural origin and further multiplied for two years at the experimental farm of DIBER field station, Auli, and afterwards, it was grown at three different altitudes, i.e., DIBER field station of Auli (2744 m), Pithoragarh (1524 m), and Haldwani (412 m), under natural field conditions. The essential oil was extracted using the Clevenger apparatus and analyzed by GC/MS and GC/FID. The total phenolic, flavonoid, and tannin content in the methanolic extracts of all the cultivations were estimated by using Folin–Ciocalteu reagent, aluminium chloride reagent, and Folin–Denis methods, respectively. The antioxidant activity of the essential oils and extracts of all the cultivations was also estimated by DPPH, ABTS, and reducing power methods. The highest amount of phenolics, flavonoids, and tannins was obtained in the Pithoragarh cultivation. Thymol was the major component in all the essential oils contributing 38.81% (Auli), 52.83% (Pithoragarh), and 31.86% (Haldwani) of the total oil. The highest antioxidant activity was exhibited by oregano oil of Pithoragarh cultivation, followed by Auli and Haldwani, respectively. The alcoholic extract of Pithoragarh cultivation had the highest antioxidant activity. The study infers that the plant demonstrated good results in terms of fresh weight, oil yield, antioxidant potential, and EO composition when grown at higher altitudes.